GENETIC ANALYSIS OF LOCAL AMAN RICE (ORYZA SATIVA L.) GENOTYPES BASED ON MORPHOLOGICAL TRAITS - Mohammad Zahir Ullah; Md. Sarowar Alam; Md. Samsuzzaman; Md Nurul Huda (Acta Scientifica Malaysia)
Rice is the staple food for the majority of the global populations and the nutritional traits improvement is the prime priority for rice breeding. The study was carried out with 30 local rice varieties including two checks during the aman season of 2021 at BIRTAN, Noakhali, Bangladesh. Significant differences were found among the cultivars for the studied parameters. The lowest days to maturity were observed in both RS 40 and RS 56. The highest grain yield per plant was observed in RS 31, followed by RS 17 and RS 22 as compared with check. The number of panicles and filled grains per panicle were the most contributing variables. Genetic distances of genotypes ranged from 0.086 to 4.262. Considering the overall diversity pattern, grain yield, and other agronomic traits, RS17, RS22, RS29, RS31, and RS42 have been selected as promising genotypes for further yield and nutritional traits improvement through hybridization.